Highly Stable 4.6 V LiCoO2 Cathodes for Rechargeable Li Batteries by Rubidium‐Based Surface Modifications. Issue 33 (17th October 2022) - Fan, Tianju; Wang, Yujie; Harika, Villa Krishna; Nimkar, Amey; Wang, Kai; Liu, Xiaolang; Wang, Meng; Xu, Leimin; Elias, Yuval; Sclar, Hadar; Chae, Munseok S.; Min, Yonggang; et al.
Abstract: Among extensively studied Li‐ion cathode materials, LiCoO2 (LCO) remains dominant for portable electronic applications. Although its theoretical capacity (274 mAh g −1 ) cannot be achieved in Li cells, high capacity (≤240 mAh g −1 ) can be obtained by raising the charging voltage up to 4.6 V. Unfortunately, charging Li‐LCO cells to high potentials induces surface and structural instabilities that result in rapid degradation of cells containing LCO cathodes. Yet, significant stabilization is achieved by surface coatings that promote formation of robust passivation films and prevent parasitic interactions between the electrolyte solutions and the cathodes particles. In the search for effective coatings, the authors propose RbAlF4 modified LCO particles. The coated LCO cathodes demonstrate enhanced capacity (>220 mAh g −1 ) and impressive retention of >80/77% after 500/300 cycles at 30/45 °C. A plausible mechanism that leads to the superior stability is proposed. Finally the authors demonstrate that the main reason for the degradation of 4.6 V cells is the instability of the anode side rather than the failure of the coated cathodes. Abstract : Enhanced stability of 4.6V LiCoO2 electrodes is achieved through application surface coating consisting of Rb, Al, and F. This coating enables effective protection of the cathode's particles from parasitic attacks and promotes the formation of robust passivation layers (SEI). Using fluorinated electrolyte solution, a high capacity of 220 mAh g −1 and impressive long‐term stability (500 cycles with 80% capacity retention) are demonstrated.